Exploring the impact of self-efficacy on glycemic control in Omani type 2 diabetes patients - AlShezawi, Ibrahim A.; Rawwad, Tamara H Al; Aldirawi, Ali A.; Alwawi, Abdallah A.; Fazari, Humoud S Al; Shah, Azmat H. (Frontiers in Endocrinology, 2025)
IntroductionSelf-efficacy is critical for diabetic patients’ adherence to self-management behaviors, including medication compliance, diet modification, physical activity, and blood glucose monitoring.ObjectivesThis study assessed diabetes self-efficacy and glycemic control among adult patients with type 2 diabetes mellitus (T2DM) in Oman and identified determinants influencing glycemic regulation.MethodsA cross-sectional study was conducted from August to October 2023. Stratified cluster sampling was used to ensure regional representation. The governorate was divided into urban, suburban, and rural strata, from which 30 health institutions were randomly selected. This method allowed practical data collection and enhanced the reliability and generalizability of results. 225 adult T2DM patients were recruited from seven clinics and public hospitals in Oman. Data were collected through a self-administered questionnaire comprising socio-demographic, clinical characteristics, haemoglobin A1c levels, and the Self-Efficacy for Managing Chronic Disease 6 Scale, a validated tool measuring patients’ confidence in managing aspects of their chronic illness, including symptoms, treatment, and emotional distress. Inclusion criteria: adults aged 18 or older, clinically diagnosed with T2DM within the last year, and able to read Arabic. Exclusion criteria: individuals who declined participation, had severe physical illness at the time of the study, or psychological disorders. Statistical analyses were performed using SPSS version 29; multiple linear regression identified predictors of glycemic control.ResultsNearly half of the patients were aged 51–70 years, most were married, and over half were female. Approximately 50% had diabetes for over a decade. The mean hemoglobin A1c was 8.23 ± 2.08, indicating moderate glycemic control, while the mean self-efficacy score was 29.99 ± 11.41 out of 60 with cut-off point 30, suggesting low self-efficacy. Significant differences in glycemic control were observed by age (p = 0.015) and marital status (p = 0.025). Additionally, patients on both oral medications and insulin had poorer control (p< 0.001), whereas those with additional chronic diseases showed better control (p = 0.049).ConclusionLow self-efficacy may contribute to inadequate glycemic control, while patients with comorbid conditions achieved better control, possibly due to heightened health vigilance and adherence. Research helps clarify these associations and informs interventions to enhance diabetes management.